Association of personality traits and emotional intelligence with risky sexual and health behaviours among adolescents in tertiary institutions in Enugu State, Nigeria - Nkechi Uzochukwu Okeke; Ifeanyi Oramadike; Henry Uchechukwu Okorie (Social Sciences and Education Research Review)
Some psychological constructs including personality traits and emotional intelligence could be vital in explaining a person's thoughts, actions, interpretations, judgements and behaviours. This study adopted correlational research design to establish the association of personality traits and emotional intelligence with risky sexual and health behaviours among adolescents in tertiary institutions in Enugu state. Four research questions guided the study. A total of 325 students in 300 and 400 levels from three selected higher institutions in Enugu state who accepted indulgence in risky sexual and health behaviours formed the sample of the study. Three sets of instruments namely